2011
DOI: 10.1007/s13277-011-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase catalytic subunit expression and proliferation index in Wilms tumor

Abstract: Telomerase activity provides telomere maintenance in chromosomes. It prevents cells from entering senescence. Telomerase activity is one of the crucial steps in various cancers. Wilms tumor (nephroblastoma) is one of the most common solid tumors of childhood. Hitherto, telomerase reverse transcriptase (TERT) catalytic subunit expression in Wilms tumor has not been investigated widely. The aim of this study was to explore the expression level of human TERT in Wilms tumor and to correlate with some clinical prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Several studies reported that ki67 positivity is associated with higher tumor stage: like the results of the present study (Juszkiewicz, 1997;Das et al, 2012;Krishna et al, 2016). Moreover, our study proved a positive relation between increased ki67 positivity and shorter disease-free survival and overall survival which is reported also by other studies (Ghanem et al, 2005;Diniz et al, 2011). However, Jurić et al reported that Ki-67 is a relevant marker for assessing the proliferative activity and tumor cell dynamics of nephroblastoma, but it may not be a good clinical prognostic marker (Jurić et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies reported that ki67 positivity is associated with higher tumor stage: like the results of the present study (Juszkiewicz, 1997;Das et al, 2012;Krishna et al, 2016). Moreover, our study proved a positive relation between increased ki67 positivity and shorter disease-free survival and overall survival which is reported also by other studies (Ghanem et al, 2005;Diniz et al, 2011). However, Jurić et al reported that Ki-67 is a relevant marker for assessing the proliferative activity and tumor cell dynamics of nephroblastoma, but it may not be a good clinical prognostic marker (Jurić et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In most reports, the lowest proliferation index was determined in the stromal component and this component generally survived after chemotherapy. 7,9,10 In the present study, we determined Cav-1 expressions confined the mesenchymal component of WTs with or without perivascular expression in the most cases. The importance of Cav-1 expression is novel and potentially relevant in WT progression, since WT1 has been identified as a suppressor of K-RAS oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Hitherto, many parameters were suggested as relevant markers for assessing the proliferative activity and tumor cell dynamics of the WT. [6][7][8][9] But the presence of Cav-1 expression in WT has not been investigated widely. The aim of this study was both to explore the importance of Cav-1 expression in Wilms tumor and also investigate the relationships between them, and some clinical prognostic factors such as tumor size, stage and histological features.…”
mentioning
confidence: 99%
“…Interestingly, 2 of our combined Wilms tumor-metanephric adenoma cases had TERT promoter mutations limited to the Wilms tumor component. High telomerase RNA expression has been associated with poor prognoses in Wilms tumor, 62 and TERT promoter mutations are thought to synergize with BRAF alterations in thyroid cancer to promote an aggressive phenotype. 63 Correlating with these findings, we did find shortening of telomeres in the Wilms tumors associated with these secondary TERT promoter mutations as well as in the metanephric adenoma components.…”
Section: Discussionmentioning
confidence: 99%